2017
DOI: 10.3319/tao.2017.01.09.01
|View full text |Cite
|
Sign up to set email alerts
|

Upper water structure and mixed layer depth in tropical waters: The SEATS station in the northern South China Sea

Abstract: The variability of the upper water hydrographic structure, the efficacy of the different schemes for estimating the mixed layer depth (MLD), the inter-comparability estimation of the MLDs and diurnal and intra-annual MLD climatology in the tropical waters in the northern South China Sea were accessed in 702 depth-profiles of potential temperature (θ) and salinity collected in 64 cruises between 17.5 and 18.5°N and 115.3 and 116.3°E from 1997 to 2013. The hydrographic structure may be subdivided into three prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
(79 reference statements)
3
10
0
Order By: Relevance
“…However, this does not necessarily mean that wind does not contribute to the vertical stratification of the water column, just that the seasonal variation of wind is not strong enough to generate the observed seasonal variation of MLD under these water column stratification conditions. This is consistent with a recent study by Tai et al (2017), who found that the intra-annual variability of MLD was mainly affected by convective overturn induced by surface cooling in winter. Moreover, the effect of wind on mixed layer dynamics can vary with background conditions.…”
Section: Journal Of Geophysical Research: Oceanssupporting
confidence: 93%
“…However, this does not necessarily mean that wind does not contribute to the vertical stratification of the water column, just that the seasonal variation of wind is not strong enough to generate the observed seasonal variation of MLD under these water column stratification conditions. This is consistent with a recent study by Tai et al (2017), who found that the intra-annual variability of MLD was mainly affected by convective overturn induced by surface cooling in winter. Moreover, the effect of wind on mixed layer dynamics can vary with background conditions.…”
Section: Journal Of Geophysical Research: Oceanssupporting
confidence: 93%
“…In contrast to the deep permanent thermocline, thermoclines and mixed layer depth (MLD) in tropical locations vary between 60 and 125 m (Figure a; Montégut, Madec, Fisher, Lazar, & Iudicone, ). This variability is seasonal in nature and shows a deepening of the MLD during the winter and a shallowing during the summer in tropical waters (Kara, Rochford, & Hurlburt, ; Tai, Wong, & Pan, ). Climate change‐related increases in sea surface temperature (SST), and reduced winds, will increase and intensify the stratification of shallow nearshore tropical waters (0–200 m), resulting in widespread shoaling of the MLD (Alexander et al, ; Behrenfeld et al, ; Capotondi, Alexander, Bond, Curchister, & Scott, ; Gittings, Raitsos, Krokos, & Hoteit, ; Signorini, Franz, & McClain, ).…”
Section: Climate Change‐related Effects On the Physical Oceanography mentioning
confidence: 99%
“…In contrast to the deep permanent thermocline, thermoclines and mixed layer depth (MLD) in tropical locations vary between 60 and 125 m (Figure 1a; Montégut, Madec, Fisher, Lazar, & Iudicone, 2004). This variability is seasonal in nature and shows a deepening of the MLD during the winter and a shallowing during the summer in tropical waters (Kara, Rochford, & Hurlburt, 2003;Tai, Wong, & Pan, 2017). .…”
Section: Climate Chang E-rel Ated Effec Ts On the Phys I C Al O Ce mentioning
confidence: 99%
“…However, differently, high seasonal correlations existed between the SChl‐a concentrations and SST and MLD, again indicating that the use of SChl‐a concentrations to represent ocean water conditions derived from satellite remote sensing may require more consideration. Considering that physical oceanographical processes such as SST and MLD are usually easier to monitor and predict changes than biological processes and that the MLD directly represents nutrient availability in the euphotic zone, especially in oligotrophic open oceans (Tai et al., 2017; Wu et al., 2003), our analysis thus emphasizes the use of MLD to represent water column phytoplankton biomass and/or primary production under climate change. Furthermore, the averaged IChl‐a concentrations were more tightly coupled with MLD than with SST, robustly demonstrating that the use of MLD could better predict oceanic Chl‐a vertical concentrations, although the aforementioned seasonal dynamics between these oceanographic variations and phytoplankton performance exist.…”
Section: Resultsmentioning
confidence: 99%